I nomi propri e gli uomini medi. Romanzo, scienze umane, democrazia - Guido Mazzoni (Between, 2015)
The rise of the genre that now we call the novel is contemporary to the development of human sciences and statistics. However, the discoursive formations of the novel and the human sciences are in many respects opposite: the novel justifies itself by presenting itself as a history of private life, as the genre of the individual; the human sciences and the statistics report individuals to the icy identity of concepts and numbers. It is as if, at the very moment in which the right to differences affirms itself, the differences were traced to the identity of the universal forces that act around and through individuals. What does this dialectic mean? What does this dialectic allows us to understand?